Analysis of Total Quality Management Implementation to Improve Managerial Performance in State-Owned Enterprises - Yudi Akhmad Sadeli (Akademi Akuntansi YKPN Yogyakarta, 2021)
This study aims to analyze the application of Total Quality Management (TQM) to improve managerial performance at the Perum Bulog Sub-Directorate of Makassar. This research is qualitative research conducted at the Office of the Bulog Subdivre Makassar. Data was sourced from interviews with informants and the results of observations and collected documentation. The informants in this study were the head of the warehousing section and the head of other sections, which consisted of 4 informants. Furthermore, qualitative data analysis was carried out in three stages: data reduction, presentation, and conclusion. The results showed that Total Quality Management is a structured system that is used to improve managerial performance. In Total Quality Management, there are improvements to the company's vision, mission, and strategy to be even better, teamwork and focus on customer satisfaction make all employees work together and try to do better in carrying out their duties so that performance management can also improve.